2010
DOI: 10.1016/j.rmed.2010.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab-induced decrease of FcɛRI expression in patients with severe allergic asthma

Abstract: The study was registered with ClinicalTrials.gov (identifier: NCT00454051) and the European Clinical Trials Database, EudraCT (identifier: 2006-003591-35).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 25 publications
(26 reference statements)
3
53
0
5
Order By: Relevance
“…The decrease in the FceRI expression on dendritic cells correlated with the decrease in its expression on basophils. Chanez et al [15], who conducted similar studies on precursor of plasmacytoid dendritic cells, made similar conclusions. However, he did not find a correlation between decreased FceRI expression and clinical parameters [15].…”
Section: Pharmacodynamic Properties Of Omalizumabmentioning
confidence: 62%
See 2 more Smart Citations
“…The decrease in the FceRI expression on dendritic cells correlated with the decrease in its expression on basophils. Chanez et al [15], who conducted similar studies on precursor of plasmacytoid dendritic cells, made similar conclusions. However, he did not find a correlation between decreased FceRI expression and clinical parameters [15].…”
Section: Pharmacodynamic Properties Of Omalizumabmentioning
confidence: 62%
“…Chanez et al [15], who conducted similar studies on precursor of plasmacytoid dendritic cells, made similar conclusions. However, he did not find a correlation between decreased FceRI expression and clinical parameters [15]. Feuchtinger et al [23] observed normalization of the number of dendritic cells in grass pollen season in patients with pollinosis allergic to grass, who underwent specific immunotherapy and were also administered omalizumab.…”
Section: Pharmacodynamic Properties Of Omalizumabmentioning
confidence: 62%
See 1 more Smart Citation
“…The studies had a broad global representation, with 10 multi-national RCTs included [13][14][15][16][17][18][19][20][21][22] . The majority of included analyses evaluated patients aged 12 years and older (15 of 26 studies) [13][14][15][16][17][18]20,[22][23][24][25][26][27] ; five trials included adults, aged 18 years and older, only 21,[28][29][30][31] , and two trials included children aged 6 to <12 years 19,32 . The majority of RCTs were large (69% had n > 300 patients).…”
Section: Summary Of Studies Includedmentioning
confidence: 99%
“…5, 6, 7 As the binding site of omalizumab overlaps with the binding site of IgE to FcεRI, omalizumab does not induce mast cell and basophil activation or anaphylactic reactions and inhibits binding of circulating IgE to its receptor on effector cells. Administration of omalizumab therefore reduces mediator release after approximately 16 weeks of therapy, which is associated with a downregulation of FcεRI expression on basophils, mast cells and antigen‐presenting cells 8, 9, 10, 11. More recently, it has been shown that omalizumab is also effective for the treatment of chronic spontaneous urticaria 12…”
Section: Introductionmentioning
confidence: 99%